2011
DOI: 10.1063/1.3601845
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of single and double spin torque oscillators

Abstract: We discuss modulation of metallic spin torque oscillators (STOs) based on single and double nano-contacts. The modulation behavior of both types of devices is characterized by equally spaced multiple sidebands, which can be ascribed mostly to a frequency modulation phenomenon. However, quantitative examination reveals that amplitude modulation is also present in both types of devices. We also show the feasibility of modulating the synchronized state of a double nano-contact STO. The synchronized state can be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Recently a more thorough analysis provided the first experimental evidence [12] of amplitude modulation. It also showed excellent quantitative agreement with a nonlinear frequency and amplitude modulation (NFAM) theory [11] as well as modulation up to 3.2 GHz [13,14,52]. It has also been shown that modulation has a general averaging effect on the non-linearity of the STO signal where modulation over regions of high frequency non-linearity results in a significant reduction (up to 90%) of the signal linewidth [16].…”
Section: Modulation Of the Propagating Modesupporting
confidence: 59%
“…Recently a more thorough analysis provided the first experimental evidence [12] of amplitude modulation. It also showed excellent quantitative agreement with a nonlinear frequency and amplitude modulation (NFAM) theory [11] as well as modulation up to 3.2 GHz [13,14,52]. It has also been shown that modulation has a general averaging effect on the non-linearity of the STO signal where modulation over regions of high frequency non-linearity results in a significant reduction (up to 90%) of the signal linewidth [16].…”
Section: Modulation Of the Propagating Modesupporting
confidence: 59%
“…In 2011, modulation of a pair of nanocontact STNOs was successfully demonstrated [159], [160], [157]. In Fig.6, we reproduce the results from [159] which show that the synchronized state of a pair of nanocontact STNOs (at 57 mA) can be maintained while modulating.…”
Section: Modulation Properties 1) Modulation Of Uniform Mode Stnosmentioning
confidence: 59%
“…In 2011, modulation of a pair of nanocontact STNOs was successfully demonstrated [159], [160], [157]. In Fig.…”
Section: Modulation Properties 1) Modulation Of Uniform Mode Stnosmentioning
confidence: 96%